Electron and Positron Impact Ionization Cross Sections of O and Hg Atoms (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
Total ionization crosssections for O and Hg atoms have been calculated for electron and positron impact scattering. A quantum mechanical formulation originating from complex atomic spherical potential is adapted in the scattering calculations on two targets. Then we obtain total ionization cross sections and cumulative total excitation cross sections by applying variant CSP-ic method. Our calculated results are presented for impact energy starting from the first threshold of ionization and going up to about 2000 electron volts (eV). For positron-atom scattering, our total inelastic cross sections include positronium formation together with ionization and excitation channels. Because of Ps formation channel it is difficult to separate our ionization cross sections from the total inelastic cross sections. An approximate method has been applied in this regard. Electron impact studies on Hg atom are scarce in literature. Similarly positron impact ionization in relation to electronic ionization discussed presently has not been highlighted much.
Keywords: Spherical complex potential; Total inelastic and total ionization cross sections; Positron impact scattering; Variant CSP-ic method